THE SPIRITUAL PERFECTION OF THE HUMAN BEING AND ONTOLOGICAL ESSENCE IN THE MYSTICAL VIEWS OF KHWAJA MUHAMMAD PARSA (Scientific journal of the Fergana State University, 2026)
This article analyzes the path to spiritual perfection and the ontological essence of the human being within the framework of the mystical (ʿirfānī) views of the renowned Naqshbandi Sufi, Khoja Muhammad Parsa. In the author's teachings, central attention is given to the perfection of the human being, purity of the heart, control of the ego (nafs), and the stages of attaining Divine Truth. The study explores how Parsa’s mystical-philosophical concepts guide the human soul toward maturity, providing an in-depth analysis of the Sufi notion of the “Perfect Human” (al-Insān al-Kāmil) and key related ideas. Furthermore, the article emphasizes the relevance of the Sufi thinker’s spiritual legacy for contemporary moral and ethical education.